Suspect Demeanor and Arrest: a Triggered Displacement of Aggression Explanation - Johnson, Richard R. (American journal of criminal justice, 2017)
The evidence that police arrest suspects who display a disrespectful demeanor is mixed. One explanation for these equivocal results may be triggered displaced aggression theory. This theory suggests persons who are provoked to anger internalize their aggression and unleash it later on someone or something that further agitates them. A sample of officers was primed for either a positive or negative affect, presented with a domestic disturbance vignette, and asked to rate their likelihood of making an arrest. In one vignette version the suspect displayed a hostile demeanor and in the other the suspect’s demeanor was neutral. Officers who were negatively primed and encountered the hostile demeanor suspect were most likely to arrest compared to officer in the other conditions.